Isolation and Identification of Vibrio parahaemolyticus Bacteria in Bottlenose Dolphins (Tursiop truncates) in Kendal Conservation Pond, Central Java - Nafiqoh, Nunak; Setiadi, Setiadi; Novita, Hessy; Lusiastuti, Angela Mariana; Indrawati, Agustin; Elmanaviean; Jannah, Siti Nur; Gardenia, Lila; Penataseputro, Tanjung; Andriyono, Sapto; Ningrum, Siti Gusti; Oktaviani, Dian; Syahidah, Dewi; Wattiheluw, Muhammad Subhan; Purwaningsih, Uni (HAYATI Journal of Biosciences, 2024)
Aquatic mammals in Indonesia are officially protected. However, there is a lack of research on these mammals, particularly in relation to potential disease-causing bacteria. A study was conducted in a conservation pond to address this gap, where swab samples were taken from the blowholes of aquatic mammals. The focus was on identifying bacteria that could potentially cause infectious diseases in these animals. The results revealed V. parahaemolyticus bacterial isolates, which showed a 98% similarity to the registered V. parahaemolyticus in NCBI. These bacterial isolates exhibited hemolysin properties and demonstrated resistance to trimethoprim, streptomycin, cephalothin, and penicillin antibiotics.